Mindfulness and media-driven prosociality: effects of trait and state mindfulness on responses to conflict photojournalism - Siqi Cheng; Sixiang Liu; Xuan Zhang; Jing Zhou; Xinran Feng (Frontiers in Psychology)
In a year where war and conflict are primarily mediated through emotionally powerful images, maintaining audience engagement without inducing compassion fatigue remains a key challenge. This study examines how trait mindfulness (a stable characteristic) and state mindfulness (induced through short- or long-term meditation) affect psychological closeness, empathy, and prosocial behavior in response to conflict photojournalism. Across three studies, we find that individuals with higher levels of trait mindfulness show greater empathy and willingness to help, even without prior meditation practice. Short-term mindfulness interventions reduce psychological distance, while long-term training enhances costly prosocial behaviors (e.g., donations, volunteering), though empathy is not necessarily increased. These results suggest that mindfulness, whether innate or trained, can enhance media-driven prosocial responses, with effects varying based on individual traits and intervention duration. The findings contribute to media psychology by revealing how mindfulness shapes the emotional and behavioral impact of war journalism, offering practical implications for ethical media presentation and audience engagement.